Corticostriatal synaptic plasticity alterations in the R6/1 transgenic mouse model of Huntington's disease - Ghiglieri, Veronica; Campanelli, Federica; Marino, Gioia; Natale, Giuseppina; Picconi, Barbara; Calabresi, Paolo (Journal of neuroscience research, 2019)
Huntington's disease (HD) is a genetic neurodegenerative condition characterized by abnormal dopamine (DA)–glutamate interactions, severe alterations in motor control, and reduced behavioral flexibility. Experimental models of disease show that during symptomatic phases, HD shares with other hyperkinetic disorders the loss of synaptic depotentiation in the striatal spiny projection neurons (SPNs). Here we test the hypothesis that corticostriatal long‐term depression (LTD), a well‐conserved synaptic scaling down response to environmental stimuli, is also altered in symptomatic male R6/1 mice, a HD model with gradual development of symptoms. In vitro patch‐clamp and intracellular recordings of corticostriatal slices from R6/1 mice confirm that, similar to other models characterized by hyperkinesia and striatal DA D1 receptor pathway dysregulation, once long‐term potentiation (LTP) is induced, synaptic depotentiation is lost. Our new observations show that activity‐dependent LTD was abolished in SPNs of mutant mice. In an experimental condition in which N‐methyl‐d‐aspartate (NMDA) receptors are normally not recruited, in vitro bath application of DA revealed an abnormal response of D1 receptors that caused a shift in synaptic plasticity direction resulting in an NMDA‐dependent LTP. Our results demonstrate that corticostriatal LTD is lost in R6/1 mouse model and confirm the role of aberrant DA–glutamate interactions in the alterations of synaptic scaling down associated with HD symptoms. Experimental models of Huntington's disease (HD), a genetic neurodegenerative condition characterized by abnormal dopamine (DA)–glutamate interactions and hyperkinesia, show alterations in synaptic plasticity in multiple brain areas. Using an in vitro patch‐clamp and intracellular recordings of corticostriatal slices from R6/1 mice, we tested the hypothesis that corticostriatal long‐term depression (LTD), a well‐conserved synaptic scaling down response to environmental stimuli, is altered in striatal spiny projection neurons (SPNs) of symptomatic R6/1 mice, a HD model with gradual development of symptoms. Our results show that, similar to other models characterized by hyperkinesia and striatal DA receptor pathway dysregulations, both synaptic depotentiation and activity‐dependent LTD are impaired in SPNs of mutant mice. Bath application of DA induced an abnormal response of D1 receptors that caused a shift in synaptic plasticity direction resulting in an N‐Methyl‐d‐Aspartate (NMDA)‐dependent LTP, in an experimental condition in which NMDA receptors are not recruited in wild‐type mice, confirming the role of aberrant DA–glutamate interactions in the defective synaptic scaling down responses associated with HD symptoms.